2015
DOI: 10.1007/s11249-015-0554-x
|View full text |Cite
|
Sign up to set email alerts
|

Friction Between Steel and Snow in Dependence of the Steel Roughness

Abstract: The purpose of this study was to analyze the effect of the surface structure on the friction between steel and snow. On a linear tribometer positioned inside a cold laboratory, four steel skis with different running surfaces were tested over a wide range of velocity, snow temperature and normal force. The surface roughness was measured with a focus variation microscope. The friction tests showed that the surface roughness had a major effect on friction between steel and snow, with higher friction for smooth su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 27 publications
4
25
0
Order By: Relevance
“…Similar tendencies about the influence of the contact area are available in other studies. A metal ski sliding over snow has shown similar results [5]. In Rohm's experiments, the tribological system is opposite to our work, i.e., snow surface is relatively constant while the used skis have different roughness.…”
Section: Sliding Speedsupporting
confidence: 59%
See 2 more Smart Citations
“…Similar tendencies about the influence of the contact area are available in other studies. A metal ski sliding over snow has shown similar results [5]. In Rohm's experiments, the tribological system is opposite to our work, i.e., snow surface is relatively constant while the used skis have different roughness.…”
Section: Sliding Speedsupporting
confidence: 59%
“…Rohm et al studied the metal samples against compressed snow, and also showed that measurement values were changing from one measurement to the next, only the observed tendency was opposite, i.e., during first runs smaller COF value was achieved and after approximately 3 runs the measurement results stabilized. It is interesting to note that this phenomenon is more noticeable on smoother surfaces [5].…”
Section: Field Sliding Experimentsmentioning
confidence: 90%
See 1 more Smart Citation
“…Figure 1 shows pictures and focus variation microscope images (Infinite Focus G4, Alicona, Austria) of the tested fabrics. The focus variation microscope images were taken to determine the roughness of the fabric's surfaces [15,16]. The images show the fabric's surface heights z(x, y) in false colors.…”
Section: Fabricsmentioning
confidence: 99%
“…Under dry/mixed friction conditions, friction typically increased with increasing roughness of the slider or ice due to increased deformative friction [4][5][6][7]. On the other hand, friction under hydrodynamic friction conditions typically decreased with increasing roughness of the slider [6,8], which was ascribed to the suppression of capillary bridges. Although the asperities facilitate the formation of capillary bridges, rougher surfaces have more volume available for the propagation of meltwater compared to smooth surfaces and also result in a smaller contact area.…”
Section: Introductionmentioning
confidence: 99%